Emotional Intelligence and Work Attitude as Predictors of Work Efficiency among Secondary School Teachers - Oladayo, Olaosebikan Thompson (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2024)
This study aimed to explore the relationship between emotional intelligence, work attitude, and job performance among secondary school teachers. The research involved 3,182 teachers and 197 principals from Junior Secondary Schools in Abia State. A sample of 40 principals and 400 teachers from 40 junior secondary schools was selected for the study. Data was collected using three research instruments: the Emotional Intelligence Scale (EIS), the Work Attitude Inventory (WAI), and the Job Performance Inventory (JPI). The EIS was adapted and the JPI from Pearce and Porter (1986). Correlation coefficients of 0.81 and 0.87 were obtained for the adapted WAI and JPI instruments, respectively, through re-evaluation using the tester-test method. Data analysis included Mean (x), Standard Deviation, Regression analysis, and Two-Way Analysis of Variance (ANOVA). Results indicated a positive prediction of job performance by emotional intelligence and work attitude among teachers. Gender was found not to significantly influence this relationship. Based on these findings, recommendations were proposed that Government and school administrators should prioritize emotional intelligence training for teachers to enhance their job performance. Additionally, ensuring a conducive working environment, regular salary payments, and opportunities for promotion were suggested to maintain positive work attitudes among teachers.